Management and Organizing Strategies in Building a Sustainable Business - Neza Aini Ariyanto; Salsabila, Nadira; Lailina, Nor Cahya; Nikmah, Wardatun; Indarti, Nunuk (International journal of technology and education research, 2026)
Business sustainability is the main focus in modern management because companies are required to be oriented not only to short-term profits, but also to long-term operational sustainability. This article discusses the strategic role of management and organizing in supporting sustainable business through a conceptual approach based on management theory. Effective management includes planning, resource utilization, and performance evaluation that ensure that each activity runs according to strategic objectives. Meanwhile, organization plays an important role in forming a work structure that is adaptive, clear, and able to respond to changes in the business environment. This article confirms that sustainability can be achieved through good governance, effective coordination, and leadership that is able to drive innovation. The use of technology, data, and a collaborative organizational culture is also a supporting factor in increasing efficiency and competitiveness. With the right integration of management and organization, the company is able to reduce risk, improve operational stability, and build long-term relationships with stakeholders. In conclusion, a targeted and adaptive managerial strategy is the key for companies to maintain business sustainability amid global competition dynamics.